Microplastics and nanoplastics in healthcare: environmental persistence, health implications, and professional awareness - Rinchuse, Daniel; Boggio, Andrea; Wilson, Nicklaus; Gastaldi, Giorgio; Manni, Antonio; Cremona, Ottavio; Cozzani, Mauro (Frontiers in Materials, 2025)
Microplastics (<5 mm) and nanoplastics (<1 μm) emerged as widespread and persistent environmental pollutants, raising growing concern for human health. These particles result from the fragmentation of larger plastic items or are directly manufactured and have infiltrated ecosystems, food, water, and air. This review examines the environmental persistence, global spread, and health implications of micro- and nanoplastics, with a particular focus on their relevance to healthcare. Special attention is given to dentistry and orthodontics, where plastic use is extensive. Microplastics have been detected in virtually all environments and even in human tissues. Although the long-term health consequences remain uncertain, emerging evidence suggests potential adverse effects, including inflammation, endocrine disruption, and toxicity, particularly from nanoplastics capable of penetrating biological barriers. The healthcare sector contributes significantly to plastic pollution through the widespread use of disposable materials. Dentistry and orthodontics generate considerable plastic waste and microplastic debris, notably from single-use items and clear aligners. However, awareness among healthcare providers remains limited, though preliminary studies indicate that education can significantly increase concern and engagement. Microplastic pollution represents a pressing environmental and public health issue. The healthcare community must acknowledge its dual responsibility, as both a contributor to and a potential mitigator of plastic pollution. Targeted education, sustainable practices, and research are urgently needed.